Evaluating of the Effectiveness of Cost Management for Employees of Oil and Gas Extraction Enterprises of PJSC "Ukrnafta" Precarpathian Basin - Камінська, І. Б. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Іn the article the model-based evaluation of the effectiveness of cost management to identify employees retrospective and predictive value efktyvnosti costs of managing teams and integrated performance indicator management costs for employees in oil and gas producing departments PJSC "Ukrnafta».